The Investigation Process of Drug-Related Crimes Based on the Criminal Procedure Code (Kuhap) Within the Jurisdiction of the Salatiga Police Resort - Nirmala Permatasari; Ridho Sa’dillah Ahmad; Lailasari Ekaningsih; Surya Kusuma Wardana; Any Farida (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
This study aims to understand the process of investigating drug-related criminal offenses based on the Indonesian Criminal Procedure Code (KUHAP) within the jurisdiction of the Salatiga Police Department. It also seeks to identify the obstacles faced in conducting the investigation of drug crimes based on KUHAP in the Salatiga Police jurisdiction and explore the solutions to these challenges. The research employs both normative juridical and sociological juridical methods, with a descriptive-analytical specification. The population and sampling method includes all objects, phenomena, events, or units that will be studied. Data collection techniques include library research and interviews, and data analysis is qualitative in nature. The steps in investigating drug-related crimes within the jurisdiction of the Salatiga Police Department are fundamentally similar to the investigation of other general criminal offenses, in accordance with KUHAP. The steps taken include: raids and arrests, searches, seizures, securing evidence, securing the crime scene, crime scene processing, evaluation, proof, and case development. Obstacles faced by law enforcement officers in investigating and resolving drug-related crimes in the Salatiga Police jurisdiction include: suspects failing to provide clear statements, witness testimonies that do not support the investigation, and incomplete evidence. Efforts to overcome these obstacles in drug crime investigations include: ensuring suspects provide clear and honest statements about the sequence of events and the drug crime objects involved, which can serve as evidence to uncover the crime; witnesses must cooperate with investigators by providing honest and complete testimonies to facilitate the investigation; investigators should work to find and gather at least two pieces of evidence in uncovering drug-related crimes; and fostering community involvement to assist in revealing drug crimes within the Salatiga Police jurisdiction.